2013
DOI: 10.1089/jmf.2012.2249
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Trial of Powdered Brassica rapa Ethanol Extract on Alteration of Body Composition and Plasma Lipid and Adipocytokine Profiles in Overweight Subjects

Abstract: We evaluated the effects of Brassica rapa ethanol extract (BREE) on body composition and plasma lipid profiles through a randomized, double-blind, and placebo-controlled trial in overweight subjects. Fifty-eight overweight participants (age 20-50 years, body mass index23.0-24.9) were randomly assigned to two groups and served BREE (2 g/day) or placebo (starch, 2 g/day) for 10 weeks. Body compositions, nutrients intake, plasma lipids, adipocytokines, and hepatotoxicity biomarkers were assessed in all subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Safety data were collected in all trials, including reports on adverse events (100%), liver function tests, renal function tests and serum biochemistry, with no differences from placebo reported. Ten trials reported on treatment‐related adverse events, and none were evident.…”
Section: Resultsmentioning
confidence: 99%
“…Safety data were collected in all trials, including reports on adverse events (100%), liver function tests, renal function tests and serum biochemistry, with no differences from placebo reported. Ten trials reported on treatment‐related adverse events, and none were evident.…”
Section: Resultsmentioning
confidence: 99%
“…The Mediterranean diet, which is characterized by a high consumption of plant-based foods, has been associated with a lower risk of cardiovascular diseases and mortality in different epidemiological studies. In the last few years, several studies, both in vitro and in vivo, have focused on the effects of Brassicaceae on chronic diseases and on the bioactive compounds of these plants that may be responsible for the observed effects [ 7 , 8 ] ( Figure 1 ). It has been discussed that the known healthy effects of Brassicaceae may be related to the presence of several bioactive compounds in the edible parts, such as ascorbic acid (AsA), phenolics, carotenoids, and glucosinolates, as summarized in Table 1 [ 9 , 10 ].…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
“…In the last few years, several studies both in vitro and in vivo have been carried out on the effects of Brassicaceae on chronic diseases [ 7 , 8 ]. By using an obese mouse model, a study demonstrated that the exposure of mice to ethanolic extracts from Brassica rapa resulted in the expression of lipolysis-related genes in white adipocytes, in the activation of cyclic AMP-dependent protein kinase, and in the induction of extracellular signal-regulated kinase, suggesting that Brassicaceae extracts may be used as safe and effective anti-obesity agents [ 11 ].…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral obesity is the most common risk factor associated with of T2DM and other chronic diseases, including atherosclerosis, arterial hypertension [ 12 ]. The modern Western diet coupled with a sedentary lifestyle has led to a pandemic of obesity which is now a severe public health issue [ 13 , 14 ]. Pharmaceutical agents with dual actions to correct hyperglycemia and promote weight are few and far between with only GLP-1 receptor agonists proving to be effective [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%